2022
DOI: 10.3390/ph15080970
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity Characterization of Novel 5-Oxopyrrolidine Derivatives with Promising Anticancer and Antimicrobial Activity

Abstract: The 1-(4-acetamidophenyl)-5-oxopyrrolidine carboxylic acid was applied for synthesizing derivatives bearing azole, diazole, and hydrazone moieties in the molecule. Modification of an acetamide fragment to the free amino group afforded compounds with two functional groups, which enabled to provide a series of 4-substituted-1-(4-substituted phenyl)pyrrolidine-2-ones. The resulted compounds 2 and 4–22 were subjected to the in vitro anticancer and antimicrobial activity determination. The compounds 18–22 exerted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Cytotoxicity assay. The in vitro inhibitory effects of the compounds were assessed using the MTT assay, as described in previous studies [24,25]. The A549 or THP-1 derived macrophages were seeded into 96-well plates at a concentration of 1 × 10 4 cells per well.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Cytotoxicity assay. The in vitro inhibitory effects of the compounds were assessed using the MTT assay, as described in previous studies [24,25]. The A549 or THP-1 derived macrophages were seeded into 96-well plates at a concentration of 1 × 10 4 cells per well.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Therefore, the development of novel antimicrobial candidates, targeting multidrug-resistant Gram-positive pathogens and drug-resistant fungi, is critically needed. Our previous studies [31,32] on the development of novel compounds targeting multidrug-resistant pathogens have been reasonably successful in finding effective antimicrobial agents and showed higher bactericidal properties than ampicillin; therefore, we have continued the studies in this field. As the results demonstrate that 5-oxopyrolidine derivatives are attractive cores for the further development of potential candidates targeting multidrug-resistant Gram-positive pathogens and drug-resistant fungi with genetically defined resistance mechanisms, herein, we report the synthesis and bioevaluation of compounds having N-(2-hydroxyphenyl)and N-(3,5-dichloro-2-hydroxyphenyl)-5-oxopyrrolidin-3-yl cores, as well their decyclization products, γ-amino acid derivatives.…”
Section: Introductionmentioning
confidence: 98%
“…Antibacterial studies of succinimide and sulphonyl moieties have also been reported. Some of the studies include 5-oxopyrrolidine derivatives against Staphylococcus aureus (Gram-positive bacterium directed activity), 30 pyrrolidine-2,5dione against Escherichia coli and Streptococcus pneumoniae, 31 N-aryl succinimide against S. aureus ATCC 25923 (Gram-positive bacterium) and K. pneumoniae 22, Salmonella 68R (Gramnegative bacterium), 32 N-sulfonamide 2-pyridones against Klebsiella pneumonia, Pseudomonas aeruginosa (Gram-negative bacterium) and Streptococcus mutans, Staphylococcus aureus (Gram-positive bacterium), 33 folic acid-sulfonamide conjugates against Gram-negative (P. aeruginosa and E. coli) and Grampositive (S. aureus and P. mirabilis) bacteria. 34 Based on the above reports and the biological importance of the succinimide moiety and sulphonyl scaffolds, significant interest has arisen in designing hybrid compounds of succinimide with sulphonyls to explore their biological activities.…”
Section: Introductionmentioning
confidence: 99%